Anticancer Drug Discovery from Natural Compounds Targeting PI3K/AKT/mTOR Signaling Pathway - Figueiredo da Silva, Manuele; Lins, Arestides Alves; Gomes, Midiane Correia; de Jesus Marinho, Washley Phyama; de Araújo, Rodrigo Santos Aquino; de Moura, Ricardo Olimpio; Zhan, Peng; dos Santos Nascimento, Igor José; da Silva Júnior, Edeildo Ferreira (Current Medicinal Chemistry, 2025)
The term cancer is used to describe a complex pathology characterized by the uncontrollable proliferation of cells, which displays a fast metastatic spread, being a disease with difficult treatment. In this context, Phosphatidylinositol 3-kinase (PI3K) represents a promising pathway to be inhibited, aiming to develop anticancer agents, since it performs a pivotal role in regulating essential cellular processes, including cell proliferation, growth, autophagy, and apoptosis. In parallel, natural compounds can effectively represent a therapeutic strategy to fight against malignant cells. Then, compounds derived from various plant sources, such as flavonoids, terpenoids, alkaloids, coumarins, and lignans, have exhibited remarkable in vitro and in vivo anticancer properties. This review focused in the exploration of natural products targeting the PI3K/AKT/m-TOR signaling pathway, demonstrating that these compounds could even further investigated to reveal novel and effective anticancer drugs in the future.
Keywords: pharmacotherapy